An anticipatory approach to quantify energetics of recycling CdTe photovoltaic systems. (11th November 2015) - Ravikumar, Dwarakanath; Sinha, Parikhit; Seager, Thomas P.; Fraser, Matthew P.
Abstract: Rapid growth in worldwide photovoltaic (PV) systems will soon result in a massive installed base of modules, electrical systems (ES), and balance of systems (BOS) that are expected to reach their end of life after two or three decades of operation. While existing recycling technologies will likely be available for steel, copper, aluminum, and other commodity materials found in the ES and BOS, these have yet to be accounted for in studies that assess the environmental impacts of PV recycling. More problematic is the lack of research identifying strategies to improve recovery of semiconductor and other module materials and develop recycling infrastructure to minimize energy required to transport these materials. The current leader in photovoltaics recycling is First Solar, which operates facilities for processing prompt scrap, breakage, and any end‐of‐life CdTe PV modules. This paper presents a comprehensive energy assessment of recycling the entire CdTe PV system based on First Solar's processes and identifies hotspots that present opportunities to improve the energy balance of future recycling operations. The energy savings derived from recycling a CdTe PV system reduces the lifecycle energy footprint by approximately 24% of the energy required to manufacture the PV system. By contrast, recycling just the CdTe PV module without the BOS has an approximately neutral net energy impact, recovering 13.2 kg of glass, 0.007 kg of Cd, and 0.008 kg of Te per m 2 . Hotspot analysis shows that reducing the energy required to recover unrefined semiconductor material from the module and ensuring high recovery of steel and glass from the end‐of‐life CdTe PV system will have the greatest impact on the energy benefits of recycling. Also, transportation energy depends on the energy tradeoff between (i) material recovery and recycling operations at the decentralized location, and (ii) transporting, recovering, and recycling the PV system components at a centralized location. An optimal strategy (centralized versus decentralized) is presented to minimize the net energy footprint when distance to the centralized recycling facility and the recycling energy requirements at the decentralized recycling facility are varied. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Energy savings from recycling reduces the CdTe PV system's lifecycle energy footprint by approximately 24% of the manufacturing energy. Recycling energy benefits can be maximized by (i) reducing module semiconductor separation energy through improved processes to separate glass from ethylene vinyl acetate encapsulant, (ii) decentralizing locations for steps 1 and 2 and centralizing locations for step 3, and (iii) increasing bulk material recovery (steel, aluminum, and copper) from the end‐of‐life PV system. 'D', 'E, and 'M' represent distance, energy, and mass flows.